What are patients actually eating: the dietary practices of cardiovascular disease patients - Ma, Yunsheng (2010)
PURPOSE OF REVIEW: To examine dietary quality for patients after a coronary heart disease (CHD) event using a selective review. RECENT FINDINGS: Poor dietary quality is a risk for patients before and after CHD events. Although cardiac rehabilitation programs often contain a nutrition education component and are advised for many patients, few patients attend cardiac rehabilitation. The American population experiences many difficulties with adherence to a higher-quality diet. A diet high in dietary quality is important in reducing risk of recurrent disease, yet few patients who have faced life-threatening cardiac events are adherent to such dietary recommendations. SUMMARY: A review of the literature indicates the need for postevent dietary evaluation and effective nutrition counseling with ongoing follow-up. In addition, we need to demonstrate the effectiveness of such approaches.